46, XX males: a case series based on clinical and genetics evaluation. (24th November 2016) - Mohammadpour Lashkari, F.; Totonchi, M.; Zamanian, M. R.; Mansouri, Z.; Sadighi Gilani, M. A.; Sabbaghian, M.; Mohseni Meybodi, A.
Summary: 46, XX male sex reversal syndrome is one of the rarest sex chromosomal aberrations. The presence of SRY gene on one of the X chromosomes is the most frequent cause of this syndrome. Based on Y chromosome profile, there are SRY ‐positive and SRY ‐negative forms. The purpose of our study was to report first case series of Iranian patients and describe the different clinical appearances based on their genetic component. From the 8, 114 azoospermic and severe oligozoospermic patients referred to Royan institute, we diagnosed 57 cases as sex reversal patients. Based on the endocrinological history, we performed karyotyping, SRY and AZF microdeletion screening. Patients had a female karyotype. According to available hormonal reports of 37 patients, 16 cases had low levels of testosterone (43.2%). On the other hand, 15 males were SRY positive (90.2%), while they lacked the spermatogenic factors encoding genes on Yq. Commencing the testicular differentiation in males, the SRY gene is considered to be very important in this process. Due to homogeneous results of karyotyping and AZF deletion, there are both positive and negative SRY cases that show similar sex reversal phenotypes. Evidences show that there could be diverse phenotypic differences that could be raised from various reasons.